2013
DOI: 10.1093/nar/gkt264
|View full text |Cite
|
Sign up to set email alerts
|

Co-transcriptional formation of DNA:RNA hybrid G-quadruplex and potential function as constitutional cis element for transcription control

Abstract: G-quadruplex formation in genomic DNA is considered to regulate transcription. Previous investigations almost exclusively focused on intramolecular G-quadruplexes formed by DNA carrying four or more G-tracts, and structure formation has rarely been studied in physiologically relevant processes. Here, we report an almost entirely neglected, but actually much more prevalent form of G-quadruplexes, DNA:RNA hybrid G-quadruplexes (HQ) that forms in transcription. HQ formation requires as few as two G-tracts instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(160 citation statements)
references
References 35 publications
6
154
0
Order By: Relevance
“…Nevertheless, it is worth thinking that the possibility that G4 structure, which can be induced by transcription (42), may modulate the ORC function in replication and/or other nuclear functions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is worth thinking that the possibility that G4 structure, which can be induced by transcription (42), may modulate the ORC function in replication and/or other nuclear functions.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of such hybrid G4 requires as few as two tandem G-tracks (guanine-rich sequences) on the nascent RNA transcript and a non-template DNA strand instead of four or more G-tracks required for formation of canonical intramolecular G4s (Figure 3B). Bioinformatic analysis identified that putative hybrid G4s are enriched within regions downstream of transcription start sites and are found in >97% of human genes, with an average of 73 putative hybrid G4s per gene 122; 123 . Formation of hybrid G4s was confirmed using T7 RNA polymerase in vitro transcription 123; 124; 125 , in vitro crosslinking, site-specific mutagenesis and transfection studies using luciferase reporters 123 .…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…Bioinformatic analysis identified that putative hybrid G4s are enriched within regions downstream of transcription start sites and are found in >97% of human genes, with an average of 73 putative hybrid G4s per gene 122; 123 . Formation of hybrid G4s was confirmed using T7 RNA polymerase in vitro transcription 123; 124; 125 , in vitro crosslinking, site-specific mutagenesis and transfection studies using luciferase reporters 123 . Results from these studies suggest that hybrid G4s inhibit transcription in vitro and represent cis –elements that are built into a gene and activated co-transcriptionally.…”
Section: Proposed Functions Of Rna G-quadruplexesmentioning
confidence: 99%
“…Recently, it was discovered by performing nascent strand sequencing that G4 sequences may also position nucleosomes at a subset of human replication origins 37 . Moreover, it was reported that Potential DNA:RNA Hybrid G-Quadruplex Sequences (PHQS) are present in > 97% of human genes, and these PHQS may modulate transcription 38 . Additional studies show that helicases, which are the molecular motors to unwind DNA and RNA, are involved in the active resolution of G4s.…”
Section: Dna G-quadruplexesmentioning
confidence: 99%